Green Capital Dynamics: Investigating the Impact of Capital Structure on Profitability among IDX LQ45 Low Carbon Leaders in Indonesia - Bustani, Bustani; Swandari, Fifi; Yunani, Ahmad (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This study explores the nexus between capital structure and financial performance among firms listed in Indonesia's IDX LQ45 Low Carbon Leaders. The study focuses on capital structure, operationalized through leverage (Total Liabilities/Total Assets), and financial performance metrics, specifically Return on Assets (ROA) and Return on Equity (ROE). Design/methodology/approach: The research employs the Hausman test to select appropriate panel data models, subsequently validated by the Breusch-Pagan test. This rigorous approach ensures robust model selection between fixed-effect and random-effect specifications. Research Findings: Based on ROA and ROE measurements, leverage's influence on financial performance does not consistently show significant statistical importance. Theoretical Contribution/Originality: This study enriches financial literature by supporting the findings of Miller and Modigliani, which indicate that capital structure does not directly impact profitability, particularly in the context of companies listed in the IDX LQ45 Low Carbon Leaders in Indonesia.